EXPLORATION OF THE POTENTIAL OF ASTERACEAE FAMILI PLANTS ETHANOL EXTRACT AS BIOLARVICIDES AGAINST THIRD-INSTAR Aedes aegypti LARVAE - Stefanus Agung Dwianto; Sri Kasmiyati; Elizabeth Betty Elok Kristiani (Berita Biologi, 2026)
The improper use of synthetic larvicides results in detrimental environmental impacts. To mitigate these effects, biolarvicides serve as a viable alternative. Plants within the Asteraceae family contain bioactive compounds with potential biolarvicidal properties. This research aimed to explore the potential of Asteraceae species as biolarvicides. This research utilizes Artemisia vulgaris, Cosmos caudatus, Eclipta prostrata, and Tagetes erecta. Extraction was conducted by the maceration method using 96% ethanol. The resulting extracts were analyzed for secondary metabolite content. Data were analyzed using SAS 9.0 software Two-way ANOVA, followed by Tukey’s post-hoc test. Larvicidal bioassays were performed on third-instar Aedes aegypti larvae at concentrations of 1,000-10,000 ppm. The parameters measured included mortality percentage, LC50, and LC90. Morphological changes in dead larvae were observed and compared against a control group. The results indicated that secondary metabolite in the leaf ethanolic extracts were higher than those in the stems and roots. The leaf ethanolic extract of C. caudatus exhibited the highest content of flavonoids (928.3±368.7 mg/g), phenolics (310.2±84.9 mg/g), tannins (187.1± 55.5 mg/g), and saponins (314±95.4 mg/g extract). Conversely, the highest alkaloid content was recorded in the leaf extract of T. erecta (27.8±7.1 mg/g). The highest mortality rate was observed in larvae exposed to A. vulgaris leaf extract, reaching 100% mortality across all concentrations within 24 hours. Consequently, LC50 and LC90 values for A. vulgaris could not be determined. For C. caudatus, the LC50 values were 7204.7 ppm (24 h) and 6839.7 ppm (48 h), while LC90 values were 9077.3 ppm (24 h) 8226.4 ppm (48 h), respectively. E. prostrata yielded an LC50 of 10255.6 ppm and an LC90 of 18048.9 ppm at 24 hours; however, these values were not detectable at 48 hours. T. erecta showed an LC50 of 6569.6 ppm (24 h) and 6397.1 ppm (48 h), with LC50 values of 9682.1 ppm and 9343.3 ppm, respectively. Morphological observations of dead larvae exposed the extracts alterations, including pigmentation, elongation, and shrinkage. While the leaf ethanolic extract of C. caudatus contained the highest concentration of secondary metabolites. The leaf ethanolic extract of A. vulgaris demonstrated the greatest potential as a biolarvicide.